Experimental Study on the Bending Performance of GFRP-Concrete-Steel Double-Skin Tubular Beams with Different Fiber Angles - Youwu Xu; Haochuan Zhu; Chongliang Du; Jian Yao (Advances in Civil Engineering)
Glass fiber-reinforced plastics (GFRP) tube-concrete-steel tube double-skin tubular beam (DSTB) is composed of an outer GFRP tube and an inner steel tube, with concrete sandwiched between two tubes. It possesses numerous advantages, including excellent ductility and corrosion resistance, lightweight, and convenient construction. Current research on DSTBs is primarily focused on the GFRP tube with an approximate ±90° fiber angle (the angle between the fiber direction and the longitudinal axis of DSTB). An experimental study on DSTBs with ±45°, ±56°, ±68°, and ±80° fiber angles was conducted under bending load. Experimental results show that the ultimate bearing capacity and deformation ability of DSTBs increases with the increase of fiber angle, the ultimate moment capacity of DSTBs with ±56°, ±68°, and ±80° fiber angles were 2.61%, 6.69%, and 6.74% higher than that of DSTB with ±45° fiber angle, respectively, the deformation ability of DSTBs with ±56°, ±68°, and ±80° fiber angles were 23.03%, 32.04%, and 38.48% higher than that of DSTB with ±45° fiber angle, respectively. However, the cracking strain decreases with the increase of fiber angle.